The environmental formation directed to the protection of the Cuban biological diversity - Ángel Caridad Lugo Blanco; Concepción Álvarez Yong; Caridad Estrada Rodríguez (Revista MENDIVE, 2017)
The environmental formation directed to the protection of the biological diversity is a topic of great present time, it is framed in a moment when the global problems and the environment derivatives of these, are in the centre of the problematic of the world environment. Cuba is not exempt of them, and it is necessary to work these topics in the school because the formation of professors constitutes a necessity, so, this article is presented and its objective is: to contribute to the environmental formation directed to the protection of the biological diversity from the General Zoology, to form these professionals in the education environmentally from the contents of this subject. General Zoology is studied in the careers of Biology-Geography and Biology-Chemistry, contributing to the development of knowledge, habits, abilities and values and it allows them to appropriate in responsible performance, in the different components of the environment, using the methods of logical theoretical, historical level and analysis and synthesis, also taking place from the theoretical analysis of the relating ones, characterization of the current state, proposing local environmental thematic that integrate these knowledge and to contribute to mitigate the loss of the biological diversity.